Menopause. A problem that is not out of date. Specialist comment and updated data from the National Consensus on the Management of Patients in Menopause - О. О. Єфіменко (Publishing House TRILIST, 2020)
Climacteric is a physiological transition period in a woman's life during which the reproductive system involutive processes against the age-related changes are dominated in the body, and characterized by reduction of menstrual and generative function due to genetically programmed cessation of ovarian function. There are 4 periods of menopause: menopausal transition period, menopause, perimenopause and menopause. This document provides an overview of existing diagnosis and treatment methods of menopausal disorders in women, proposed algorithms for diagnosis and treatment of this disease to prevent heart diseases, osteoporosis and improve the quality of ukrainian women life. No need for hormonal laboratory research to diagnosis of perimenopause and menopause for most healthy women aged over 45 with the following features: vasomotor symptoms on a background of irregular menstruation in perimenopause; absence of menstruation for the last 12 months or appearance of menopausal symptoms after hysterectomy at menopause. The most common symptoms of menopause are vasomotor symptoms (hot flashes, night sweats, palpitations, labile blood pressure); psychological (emotional lability, depression, anxiety, irritability, sleep disturbances, poor memory and concentration); general physical symptoms (asthenia, headache, pain in muscles and joints, skin discomfort); urogenital and sexual (vaginal itching, burning, dryness and dyspareunia, frequent and urgent urination, decreased libido). The only pathogenetically effective method for the correction of menopausal disorders is menopausal hormone therapy. For this therapy are used natural estrogen (17β-estradiol, estradiol valerate, estriol) in combination with progestins (dydrogesterone) or androgens. It is possible parenteral (injections), transdermal, vaginal and oral hormone introduction. To correct the climacteric syndrome, urogenital disorders are used short courses of menopausal hormone therapy (for 1-5 years). For the prevention and treatment of osteoporosis menopausal hormone therapy lasts over 3 years if necessary, in combination with a bisphosphonate.